Risk Assessment and Control Tool for P-hailing Industry in Malaysia - Chia, Jia Mei (2025)
As known, the number of p-hailers has increased with the development of the gig economy after the COVID-19 pandemic. Due to the nature of the working environment, the number of incidents involving the p-hailers is high and there is negligence on the p-hailers’ benefits. The main objective of this study is to develop a risk assessment and control tool for the p-hailing sector. The first specific objective of this study is to construct a framework of risk assessment and control tool for the p-hailing sector. Next, to validate the framework of the risk assessment and control tool for the p-hailing sector via expert feedback. Thirdly, to develop a risk assessment and control tool based on the framework constructed for the p-hailing sector and lastly to test the risk assessment and control tool via case studies. In order to protect the p-hailers from hazardous working environments, this research performed Hazard Identification, Risk Assessment, and Risk Control (HIRARC) to reduce the risk faced by the p-hailers. Beginning with the DOSH-guided HIRARC framework, then content validation is carried out by experts to validate the tool content. The result from content validation shows that all three experts are satisfied with most of the items found in the developed tool because all the CVI values are almost 1, which is in line with the acceptable CVI values. The tool is developed as a website using XAAMP as server, Visual Studio Code as PHP code editor and MySQL as database. SUS questionnaire is used to identify whether this tool is acceptable or not. The users are the p-hailers. The overall average SUS score was 79.75, with acceptability ranges "Acceptable". The scale is an "A-," with a "Good" rating on the model adjectives. This result shows that the tool is acceptable to its users and meets usability criteria. The interview method was used by asking the users to answer three open-ended questions. Most of the users provide positive responses to the questions. The tool received comments such as easy to use, convenient and time-saving. It is hoped that the tool can be used to reduce the prevalence of incidents occurring among the p-hailers.